Strategi Perencanaan dan Pengelolaan Keuangan Desa dalam Rangka Implementasi PP RI No. 4 Tahun 2017 - Erfit; Dwi Hastuti; Haryadi; Zulgani; Emilia (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community engagement activity aims to improve village financial management based on the Republic of Indonesia Government Regulation No. 4 of 2017 concerning the Determination of Village Fund Usage Priorities. The research identifies the importance of village financial management for village officials in enhancing their individual and institutional capacity to utilize the village fund effectively and transparently. Additionally, the study analyzes the changes in regulations regarding the village fund made by the government to promote economic growth in the villages. By granting autonomy to villages, the government provides significant opportunities for them to manage governance and development according to their needs and priorities. This enables the development of creativity and potential among the community, ultimately enhancing welfare and the quality of life in the villages. Consequently, the research also aims to analyze the impact of village autonomy on financial and asset management, strengthening village governance independence. During the guidance and consultation activities for village financial management, the researchers compile guidelines and references based on the regulations issued by the Minister. These guidelines are expected to improve the quality and accountability of village finances and encourage effective governance of village tasks and functions. The results of this research are expected to provide benefits by enhancing the efficiency and effectiveness of village financial management, thereby optimizing the village fund and generating positive impacts on development and the welfare of the village community.